Role-play simulations for climate change adaptation education and engagement - Rumore, Danya; Schenk, Todd; Susskind, Lawrence (Nature Climate Change, 2016)
Science-based role-play simulation exercises involving face-to-face mock decision-making have potential as education and engagement tools for enhancing readiness to adapt to climate change, as results from two research projects show.